Der deutsch-türkische Bildungsraum im Wilhelminischen Kaiserreich Akteure, Netzwerke, DiskurseAkteure, Netzwerke, Diskurse - Böttcher, Julika (Wie die Türken in unsere Köpfe kamen. Eine deutsche Bildungsgeschichte, 2023)
Today's ignorance of German-Turkish relations before the 1961 recruitment agreement stands in astonishing contrast to the attention paid to the Ottoman Empire before and during the First World War. Using a variety of previously unknown historical sources, the author reconstructs how German pedagogy and teachers in the Wilhelmine Empire contributed to the shaping of a German-Turkish educational space. To this end, she takes a transnational perspective on the actors, networks, and discourses that flanked Germany's world power ambitions at the time in terms of cultural policy. With her study, she makes an insightful contribution to the postcolonial historiography of pedagogy and educational science.